Алгоритми визначення станів рівноваги економічної системи за наявності монополістів та з різними типами поведінки споживачів - Makhort, Andrii P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The equilibrium model of Walrassian type is applied to a description of a reaction of an economy system on an influence of selected factors. The research involves an adaptation of an equilibrium problem in case of an economy with different behaviours of consumers to use simpler solving methods that correspond to the case of exclusively insatiable consumers in the economy. An application of iterative methods for solving the economy equilibrium problem is justified. The conditions on the specified model characteristics that lead to a convergence of the iterative methods are presented. The proposed algorithm that determines the equilibrium characteristics allows to determine the conditions for reaching equilibrium states with specified properties.